Coping Mechanisms of Previously Diagnosed and New HIV-Discordant, Heterosexual Couples Enrolled in a Pilot HIV Self-Testing Intervention Trial in Central Uganda - Matovu, Joseph K. B.; Kisa, Rose; Malek, Angela M.; Vrana-Diaz, Caroline; Mukama, Semei Christopher; Musoke, William; Korte, Jeffrey E.; Wanyenze, Rhoda K. (Frontiers in Reproductive Health, 2021)
Introduction: Learning that a couple has HIV-discordant results can create tensions in the relationship including separation. We explored the coping mechanisms of HIV-discordant, heterosexual couples enrolled in an HIV self-testing (HIVST) intervention trial in Central Uganda. Materials and Methods: This qualitative study was nested within a pilot HIVST intervention trial targeting pregnant women and their male partners in central Uganda. In-depth interviews were conducted with 18 individuals from 13 HIV-discordant couples between July and September 2018; 18 months after the end of the main trial. Data were collected on the couples' initial reactions after learning about their HIV-discordant status, mechanisms adopted by couples to cope with HIV-discordance, and suggestions on how couples in similar situations can be supported. Interviews were transcribed verbatim and analysed manually following a thematic framework approach. Findings: Of the 13 HIV-discordant couples, the female partner was HIV-positive (M–F+) in seven, while the male partner was HIV-positive (F–M+) in six. The mean (±SD) age of the participants was 32.6 (±6.4) years and participants had stayed together for an average of 5.5 (±3.6) years. Fourteen participants from nine couples already knew about their HIV-discordant status by the time they participated in the HIVST trial. After learning about their HIV-discordant status, most individuals (15) thought of abandoning their relationship; three (3) thought of committing suicide. To cope with HIV-discordance, some couples reported that they sought professional counselling support from healthcare providers, and this was particularly true for couples that were already aware of their HIV-discordant status by the time they participated in the HIVST trial. However, new couples that learnt about their HIV-discordant status after participating in the trial reported that they sought psycho-social support from friends or relatives. In the majority of cases, couples reported that they reduced the frequency of sex or abstained from sex. Some couples temporarily separated from their partners, while a few others resorted to using condoms to reduce HIV infection risk. Conclusion: Couples used a variety of approaches to cope with HIV-discordance. Study findings underscore the importance of ongoing professional counselling and psycho-social support in helping couples to cope with HIV-discordance.